Bone mineral density and body composition in Australians following plant-based diets vs. regular meat diets - Austin, Grace; Ferguson, Jessica J. A.; Eslick, Shaun; Oldmeadow, Christopher; Wood, Lisa G.; Garg, Manohar L. (Frontiers in Nutrition, 2024)
Background and aims Bone mineral density (BMD) and body composition play an important role in maintaining metabolic health and physical functioning. Plant-based diets (PBDs) are known to be lower in protein and calcium, which can impact BMD and body composition. This study aimed to investigate the relationship between various PBDs compared to regular meat diet and whole-body BMD, body composition, and weight status. Methods A cross-sectional study was conducted with adults (n = 240) aged 30–75 years, who habitually followed dietary patterns: vegan, lacto-vegetarian, pesco-vegetarian, semi-vegetarian, or regular meat eater (48 per group). Parameters were measured using dual-energy x-ray absorptiometry (DXA), and multivariable regression analyses were used to adjust for lifestyle confounders, socioeconomic factors, and BMI. Results After adjustments, whole-body BMD and body composition were not significantly different between those following PBDs and regular meat diets, except for lacto-ovo vegetarians, who had significantly lower lean mass by −1.46 kg (CI: −2.78, −0.13). Moreover, lacto-ovo vegetarians had a significantly lower T-score by −0.41 SD (CI: −0.81, −0.01) compared to regular meat eaters. Waist circumference was significantly lower in individuals adhering to a PBD compared to a regular meat diet: vegans by −4.67 cm (CI: −8.10, −1.24), lacto-ovo vegetarians by −3.92 cm (CI: −6.60, −1.23), pesco-vegetarians by −3.24 cm (CI: −6.09, −0.39), and semi-vegetarians by −5.18 cm (CI: −7.79, −2.57). There were no significant differences in lean mass (%), fat mass (% and total), android/gynoid measures, body weight, or BMI across dietary patterns. All dietary patterns met the recommended dietary intake for calcium and protein, and 25-hydroxy-vitamin D status was comparable across groups. Conclusions This cross-sectional study found that adhering to a PBD characterized by varying degrees of dairy and meat restriction is not associated with meaningful changes in BMD or body composition, provided that the dietary patterns are planned appropriately with adequate levels of calcium and protein.